Extension and advice: Technology retains talent - Stam, Gertjan van (Technical Centre for Agricultural and Rural Cooperation, 2011)
With little access to formal extension services, a rural Zambian community set up an internet connection to develop local agriculture, education and energy facilities. The community is now using local radio to encourage other villages to do the same